Mechanical performance and long-term indoor stability of polyhydroxyalkanoate (PHA)-based wood plastic composites (WPCs) modified by non-reactive additives. (January 2018) - Chan, Clement Matthew; Vandi, Luigi-Jules; Pratt, Steven; Halley, Peter; Richardson, Desmond; Werker, Alan; Laycock, Bronwyn
Graphical abstract: Highlights: BN and talc increases the rate of crystallisation of the wood-PHBV composites. Wood-PHA composites are mechanical stable at ambient temperature for at least 1 year. Talc offers complementary space-filling morphology and improves composite stiffness. The level of stiffness improvement from talc is reduced after 1-year of ageing. A mechanism for the weakened talc-PHBV interface upon ageing is proposed. Abstract: This study aims to understand the material properties and long-term indoor stability of a biocomposite based on pine wood flour and poly(3-hydroxybutyrate- co -3-hydroxyvalerate) (PHBV) modified by a nucleating agent, boron nitride (BN), and an inorganic filler, talc, and to develop knowledge of the linkage between the microscale-structure and mechanical properties. Both BN, at a loading of 1 wt% and talc, at 5 wt%, had a nucleating effect on polymer crystallisation, with BN being more effective as evidenced by Avrami kinetic analysis. The addition of 5 and 10 wt% of talc enhanced the tensile strength of the PHBV/wood flour (50/50 wt%) composite from 22.3 ± 1.3 MPa (mean ± 95% confidence interval) to 24.3 ± 0.6 MPa and 24.7 ± 0.9 MPa respectively. The tensile modulus was also improved from 5.6 ± 0.6 GPa to 6.9 ± 0.4 GPa and 8.1 ± 0.7 GPa respectively. The micron-sized talc may fill voids within the composite matrix and/or act as an alternate filler, altering the deformation mechanism. However, the level of improvement in modulus was reduced after 1 year of conditioned ageing under a controlled environment (20 °C, 50% humidity). It is proposed that the combined effects of the swelling of wood through moisture uptake, the shrinkage of PHBV through secondary crystallisation, and the localised stress around talc particles led to weakened talc-PHBV interfaces.